How Significant is the Role of Social Media in Driving the Marketing Performance of MSMEs in the F&B? - Rahmawati; Tikawati; Bayu, Muhammad; Fadelan, Nahwani; Purwanto, Sayugo Adi; Puspitasari, Lisa; Nurhidayati, Safitri (Jurnal Mebis, 2025)
This study seeks to investigate the impact of technology resources, managerial support, and halal brand leverage on marketing success, with social media usage acting as a moderating variable. The respondents of this study consisted of 110 micro, small, and medium-sized enterprises (MSMEs) in the food and beverage (F&B) industry from East Kalimantan. Data were collected through an online survey by distributing questionnaires in the form of Google Forms to eligible MSMEs. The collected data were then investigated using descriptive statistics and Partial Least Squares Structural Equation Modelling (PLS-SEM). The hypothesis testing indicates a balanced result: of the six formulated hypotheses, three are substantiated while three are not. Specifically, technological resources and halal brand leverage are found to exert a significant influence on marketing performance, whereas management support does not exhibit a significant effect. The moderating role of social media usage was evident only in the relationship between halal brand leverage and marketing performance. In contrast, social media usage does not operate as a moderator in the relationship between technological resources and marketing performance or between management support and marketing performance. The findings of this study can serve as a basis for providing strategic interventions for MSMEs, enabling them to improve their marketing performance amid intensifying competition.